Kreativitas Perempuan Jawa Dalam Pencarian Nafkah Rumah Tangga Di Desa Bungadidi - Lisdawati; Riri Amandaria (Research Agency for Humanity and Urban, 2023)
This study aims to find out about: 1) Factors that cause Javanese women to earn a living in the household; 2) The strategy for Javanese women to make a living in the household; 3) the role of Javanese women in earning a living as well as housewives. In this study, researchers used a descriptive qualitative research type. The selected informants were Javanese women who worked to help the household economy. The researchers collected data by means of observation, interviews and documentation. The results of the study showed that: 1) the factors that caused Javanese women to earn a living in the household included low family economy and less income for their husbands. While the difficulties faced by working Javanese women include internal time management factors, as well as external factors such as husband's support and work problems; 2) The strategy for Javanese women to make a living in the household, namely (a) The active strategy is a survival strategy carried out by Javanese women, namely working as vegetable traders and sego pecel traders. Javanese women work to help increase the family's economic income (b) The passive strategy carried out by Javanese women is to try to apply frugal patterns in household expenses c) The network strategy is survival which is done by asking for help from relatives or friends. Javanese women make efforts to utilize relations and connections between family and friends